American Crow Brain Activity in Response to Conspecific Vocalizations Changes When Food Is Present - Pendergraft, LomaJohn T.; Marzluff, John M.; Cross, Donna J.; Shimizu, Toru; Templeton, Christopher N. (Frontiers in Physiology, 2021)
Social interaction among animals can occur under many contexts, such as during foraging. Our knowledge of the regions within an avian brain associated with social interaction is limited to the regions activated by a single context or sensory modality. We used 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) to examine American crow (Corvus brachyrhynchos) brain activity in response to conditions associated with communal feeding. Using a paired approach, we exposed crows to either a visual stimulus (the sight of food), an audio stimulus (the sound of conspecifics vocalizing while foraging) or both audio/visual stimuli presented simultaneously and compared to their brain activity in response to a control stimulus (an empty stage). We found two regions, the nucleus taenia of the amygdala (TnA) and a medial portion of the caudal nidopallium, that showed increased activity in response to the multimodal combination of stimuli but not in response to either stimulus when presented unimodally. We also found significantly increased activity in the lateral septum and medially within the nidopallium in response to both the audio-only and the combined audio/visual stimuli. We did not find any differences in activation in response to the visual stimulus by itself. We discuss how these regions may be involved in the processing of multimodal stimuli in the context of social interaction.